Nur Halimah Analisis Pengaruh Deposito Dan Pembiayaan Musyarakah Terhadap Return On Asset (ROA) Pada Bank Syariah Indonesia (BSI) Periode 2021-2023 - Nur Halimah (JIBF MADINA : Journal Islamic Banking and Finance Madina, 2024)
This research aims to find out how much influence deposits have on ROA, the influence of musyarakah financing on ROA and the influence of deposits and musyarakah financing together on ROA at Bank Sayriah Indonesia. This research uses a quantitative approach with secondary data. The population in this research is all financial reports of Bank Syariah Indonesia which have been published on their official website. The sample in this research is the financial position report and profit and loss report and loss ratio calculation report from 2021-2023. The sampling technique in this research uses the Purposive Sampling method. The dependent variable (Y) in this research is Return On Assets, the independent variables are deposits (X1), musyarakah financing (X2). The tool used in this research is SPSS version 20. Based on the results of SPSS calculations, research results show that deposits do not have a positive and significant effect on ROA at BSI, this is proven by the value of tcount < from ttable, namely tcount -0.389 < ttable 1.833, with a significance value of 0.700 > 0.05. Musyarakah financing has a significant effect on ROA at BSI, this is proven by the tcount value of X2= 4.189 and ttable 1.833. So tcount>ttable (4.189>1.833), with a significant value of 0.002 <0.05. Then the research results show that deposits and musyarakah financing simultaneously or jointly influence ROA at BSI, this is proven by the calculated F value of 19.402> F table 4.256 (19.402>4.256), with a significance value of 0.001 < 0.05. Keywords: Deposits, Musyarakah Financing, Return On Assets (ROA)